Opera in South Africa during the first democratic decade - Meredith, Ivan (College of Music, 2018)
The author set out to investigate operatic works that were written in South Africa between 1994 and 2004. Original works that included African elements were of interest as was their classification as operas, musical theatre or music drama. Their artistic merit and the process followed in writing successful works in this genre were investigated. Not only was the collaboration between composer and librettist scrutinised, but also the initial stage during which the conception for these theatrical works took shape. Due to the empirical nature of the research, data was collected mostly via interviews held with composers, librettists, directors and conductors of original works written and performed in the said period. The data is presented in six chapters, each one providing a full description of casting details, synopses and brief analyses of the works. In the Preface the premise upon which the research rests is discussed, while the Introduction serves to highlight various issues concerning modem opera and fusion works that have played an important role in providing the groundwork for contemporary ethnic opera in this country. Original works are discussed in each chapter, and a critical evaluation is presented in an Appendix. The author concludes that much effort was expended by pioneers in the fields of music, theatre and dance to create new works and organise performances. What emerged, furthermore, was that many of the works analysed could not be categorised as 'opera' but rather as 'musical theatre' or 'music drama'. It would also seem that uninitiated audiences first need to be made conscious of the aesthetic value of the genre before they may be able to appreciate it. Operatic production companies have always been at the forefront when it comes to decision - making regarding which and whose work shall be performed. Funding is crucial to the success of any production and plays an equally important role in eventually determining a positive outcome. This aspect has, therefore, also been included as part of the research project.